As-Saja’ Fî Al-Juz’i Al-Tsalâtsîn Min Al-Qur’ân Al-Karîm - Atifa Anami; Rehani Rehani (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2021)
The Qur’an has a variety of language styles that make the reading beautiful to hear which is reflected through the similarity of sounds at the end of each verse in the Qur’an, one of which is poetry. Poetry plays a role in beautifying the language of the Qur’an. Poetry is one of the branches of balaghah in the study of badi’ science which is studied in Arabic learning. The purpose of this study was to determine the number of poems contained in juz 30 in the Qur’an al-karim as well as the kinds and signs that exist in juz 30. In this study, the researcher uses the descriptive analysis method, because the researcher analyzes, describes, and explains the poems contained in the Qur’an, especially in juz 30. The results of the study show that number of poems in juz 30 is 99 poems. As for the kinds of poems in juz 30, is three kinds of poems, namely mutharraf’s poems have 86 poems and mutaeFRwazi’s poems have 10 poems and murassha’ poems have 3 poems. As for the signs, there are also three according to the type of rhyme, namely the mutharraf rhyme sign is the difference in the last word in terms of wazan and the suitability of the final letter. The mutawazi rhyming is the compatibility of the last word in terms of wazan and the final letter. As for the sign in the murassha’ rhyme is the compatibility of all or part of the lafadz in two or more sentences in terms of wazan and the final letter